2021
DOI: 10.3390/brainsci11070925
|View full text |Cite
|
Sign up to set email alerts
|

Rat Models of Vocal Deficits in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a progressive, degenerative disorder that affects 10 million people worldwide. More than 90% of individuals with PD develop hypokinetic dysarthria, a motor speech disorder that impairs vocal communication and quality of life. Despite the prevalence of vocal deficits in this population, very little is known about the pathological mechanisms underlying this aspect of disease. As such, effective treatment options are limited. Rat models have provided unique insights into the disease-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 164 publications
(217 reference statements)
0
10
0
1
Order By: Relevance
“…Previous work has demonstrated operant conditioning can progressively increase the number of USVs produced by rats over multiple weeks (Johnson et al, 2011). This operant conditioning paradigm is a useful model for investigating the effects of increased laryngeal muscle use on USV acoustic characteristics and underlying central and peripheral laryngeal sensorimotor mechanisms (Johnson et al, 2013;Lenell et al, 2019;Krasko et al, 2021;Shembel et al, 2021). However, previous work relied on manual training by hand to elicit USV productions (Johnson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated operant conditioning can progressively increase the number of USVs produced by rats over multiple weeks (Johnson et al, 2011). This operant conditioning paradigm is a useful model for investigating the effects of increased laryngeal muscle use on USV acoustic characteristics and underlying central and peripheral laryngeal sensorimotor mechanisms (Johnson et al, 2013;Lenell et al, 2019;Krasko et al, 2021;Shembel et al, 2021). However, previous work relied on manual training by hand to elicit USV productions (Johnson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…USVs are produced within the larynx and require fine motor control of the intrinsic laryngeal muscles (Kelm-Nelson et al, 2018). These USVs are valuable biomarkers for studying behavioral and mechanistic changes in a variety of diseases and disorders, such as Parkinson's disease, autism, and age-related voice disorders (Johnson et al, 2015;Caruso et al, 2020;Krasko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the preformed αsyn fibril mediated rat model, formation of end stage αsyn aggregates coincided with the vocalization deficits. These vocal deficits scaled with the extent of αsyn-related neuropathology [ 28 , 29 ]. However, due to a limited understanding of the neural circuitry for rodent vocalizations, especially the cortico-basal ganglia-thalamo-cortico loop, studies employing model systems with well-characterized vocal circuits that can be directly targeted are necessary for understanding diseases affecting voice and speech, including PD and Huntington’s disease [ 7 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rodents have identified links between impaired vocalizations and PD neuropathology [ 18 25 ]. For instance, vocal deficits were reported in the virally-mediated rat model overexpressing human wild-type αsyn, in a transgenic mouse model of PD overexpressing human wild-type αsyn under the broad neuronal promoter Thy-1, and in a rat model where preformed αsyn fibrils were injected directly into the striatum [ 26 29 ]. Rats injected with an adeno-associated virus (AAV) to target overexpression of human wild-type αsyn in substantia nigra, which provides input onto basal ganglia, exhibited impaired call rate and reduced call intensity [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Otra opción de uso de la sonificación en contextos terapéuticos se sitúa en el interés de estudios preclínicos relacionados con el estudio de la voz como transmisora de información más allá de los lingüístico. El estudio de las características sonoras de vocalizaciones en animales no humanos, ha permitido hasta el momento explorar otros índices de emoción y motivación en estudios de investigación con roedores, importantes para el avance del conocimiento en enfermedades como el Parkinson (Krasko et al, 2021) o la depresión (Brudzynski, 2019).…”
unclassified